Properties of α-expansions of topologies - David A. Rose (International Journal of Mathematics and Mathematical Sciences)
The results of O. Njåstad for α-topologies together with the results of P. L. Sharma for anti-compact perfect Hausdorff spaces are combined to produce several counterexamples in one space.